The relationship between entrepreneurship education and entrepreneurial intention: evidence from a transition country. (24th August 2021) - Çera, Edmond; Çera, Gentjan; Skreli, Engjell
Finding ways that foster entrepreneurship is a constant concern for policymakers. Education is seen as a key factor that may contribute in this regard. This study seeks to assess the relationship between entrepreneurship education and entrepreneurial intention in the context of a transition country. Using a dataset of 528 respondents, two groups (treated and controlled) were created following a quasi-experimental research design. To ensure the comparability of these two groups, propensity score matching and coarsened exact matching were performed. The study found a positive relationship between entrepreneurship education and entrepreneurial intention, which is consistent with previous studies. This research provides useful insights for policymakers and universities who are responsible for designing policies or curricula to encourage students to engage in entrepreneurial activities.